Development of creep and shrinkage prediction model for Malaysian normal strength concrete - Khoo, Hui Kiang (2006)
A study was conducted to investigate the degree of accuracy of creep and shrinkage prediction models developed in other countries applied to Malaysian concrete. Currently, creep and shrinkage strains for Malaysian concrete are predicted using foreign standard codes and prediction models developed in temperate countries. As creep and shrinkage are influenced by many factors including the constituent materials, temperature and relative humidity of the environment, it is therefore essential to study the appropriateness of using these models for Malaysian concrete. In this study, the test results obtained from concrete specimens having characteristic compressive strength of 20, 30 and 40N/mm2, respectively and loaded at 7 days and 28 days were compared with Eurocode 2 (EC2), ACI 209 model (developed by American Concrete Institute), CEB-FIP 90 model (developed by Euro-International Concrete Committee and International Federation for Prestressing), B3 model ( developed by Z. P. Bazant and S. Baweja), GL2000 model (developed by N. J. Gardner and M. J. Lockman ) and Australian Standard code model (AS3600). From the study, AS3600 code model and B3 model were found giving the best prediction for creep and shrinkage, respectively. However, CEB-FIP 90 model was preferred than AS3600 code model as AS3600 code model predicts creep by interpreting graph, thus the accuracy of the predicted values are questionable. Modification factors were proposed to CEB-FIP 90 model and B3 model for predicting creep and shrinkage strains of Malaysian normal strength concrete.